2014
DOI: 10.11648/j.ajmp.20140303.14
|View full text |Cite
|
Sign up to set email alerts
|

Kinematical Brownian Motion of the Harmonic Oscillator in Non-Commutative Space

Abstract: In this work the Jacobi's second equality in the form of stochastic equation and the Wiener path integral approach are used to evaluate the probability density of harmonic oscillator in non-commutative space. Using the factorization theorem and the Mastubara formalism, the thermodynamic parameters are determined. The structure of Fokker-Planck equation remained the same even in a commutative and non-commutative space. Moreover, the noncommutative parameter is depicted for increasing value of the entropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Furthermore, Tchoffo et al in their investigation on kinematical Brownian motion of harmonic oscillator in NC space showed that the structure of Fokker Planck's equation is not modified (i.e. the factorization theorem is conserved in both commutative and NC space) [31]. More recently, Santos et al have introduced the Brownian motion of a particle in two-dimensional NC space using the standard NC algebra embodied by Weyl-Moyal formalism to find that, NCity induces a non-vanishing correlation between both coordinates at different times [32].…”
mentioning
confidence: 99%
“…Furthermore, Tchoffo et al in their investigation on kinematical Brownian motion of harmonic oscillator in NC space showed that the structure of Fokker Planck's equation is not modified (i.e. the factorization theorem is conserved in both commutative and NC space) [31]. More recently, Santos et al have introduced the Brownian motion of a particle in two-dimensional NC space using the standard NC algebra embodied by Weyl-Moyal formalism to find that, NCity induces a non-vanishing correlation between both coordinates at different times [32].…”
mentioning
confidence: 99%